The function of autophagy as a fundamental process of preserving cell homeostasis - Nikolina Elez-Burnjaković; Lejla Pojskić; Sanin Haverić; Ajla Smajlović (Биомедицинска истраживања, 2021)
Autophagy is a dynamic process, conserved in all eukaryotes. It is responsible for the degradation of cytoplasmic content. Autophagy is crucial in cell survival and cell death. It plays a significant role in the cell response to stress, nutrient deficiencies, embryonic development, tumor suppression, response to pathogens and aging. The process of autophagy is also involved in the pathology of human diseases, such as cancer, diabetes, cardiomyopathy, and neurodegenerative diseases such as Alzheimer's and Parkinson's disease. Autophagy is a mechanism that involves degradation of cells, proteins, damaged organelles and pathogens through the lysosomal mechanisms, thus autophagy supports cell survival during starvation, hypoxia and metabolic stress. However, if extensive and/or excessive, autophagy can promote apoptosis (type I) or function as an alternative cell-death pathway, called autophagic cell death (type II). Autophagy can either promote cancer cell death, or serve as a survival mechanism against apoptosis or necrosis induced by various anticancer treatments. Given the contradictory role of autophagy during tumor initiation and progression, the use of autophagy in therapy depends on the context and must be approached individually
Keywords: autophagy; cell survival; cell death; tumor